Digital Curation and Archival Science: a look to the digital record - Silva, Amanda Marissa Soares da (2021)
The article aims to reflect on the views of Archival Science and Digital Curation regarding the digital record. It is observed that Digital Curation has stood out in contemporary times for performing data management and preserving digital documents. In this sense, it is questioned the differences and possible relationships between Archival Science and Digital Curation. Amid this discussion, features that are inherent to the record stand out and that must be guaranteed for its effective meaning, which is authenticity and reliability. It is known that Archival Science is based on the studies of Contemporary Diplomatics for the establishment of theoretical and methodological support to guarantee reliability. As regards the methodology, theoretical research of a descriptive and exploratory character is carried out, which seeks to discuss the concepts of Digital Curation and Archival Science in the literature to respond to the proposed objectives. Finally, it was possible to perceive that the look given to the digital records by Digital Curation differs from that of Archival Science, mainly because it does not stick to the characteristics that give meaning to the digital record.